2009
DOI: 10.1007/s12565-009-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

The eosin-shadow method: a selective enhancement of light-microscopic visualization of pancreatic zymogen granules on hematoxylin–eosin sections

Abstract: We developed a novel method for enhancing light-microscopic visualization of pancreatic zymogen granules in a selective manner on hematoxylin and eosin-stained sections. By using an absorption filter that transmits light with wavelength from 510 to 550 nm, corresponding to the narrow absorption spectrum of eosin, only eosinophilic tissue and cellular components were remarkably highlighted as distinct shadows against lighter background consisting of basophilic components. Using a pair of mirror sections of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…It was previously shown that autofluorescence of eosin Y in H & E-stained pancreatic sections provides an excellent method for selectively identifying acinar cell zymogen granules (37,39). Fluorescence analysis of pancreatic sections confirmed our previous report (1) that TPN induces a striking loss of granular staining in the apical cytoplasm of acini indicating a loss of zymogen granules (Fig.…”
Section: Resultssupporting
confidence: 87%
“…It was previously shown that autofluorescence of eosin Y in H & E-stained pancreatic sections provides an excellent method for selectively identifying acinar cell zymogen granules (37,39). Fluorescence analysis of pancreatic sections confirmed our previous report (1) that TPN induces a striking loss of granular staining in the apical cytoplasm of acini indicating a loss of zymogen granules (Fig.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, no zymogen granules are detected using fluorescent eosin staining (Fig. 2C), which would indicate the presence of pepsinogens 31 . However, gene expression analyses revealed that the genes encoding the catalytic α-subunit ( atp4a) and the non-catalytic β-subunit ( atp4b) of H + /K + ATPase are expressed in the epithelium of the prospective stomach from st.27 onwards (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…canicula and detect the presence of acid mucins (blue) and neutral-acidic mucins (magenta). Eosin fluorescence allowed visualization of eosinophilic zymogen granules typically found in the acinar cells of gastric glands 31 . Immunohistochemistry (IHC), with rabbit polyclonal antibody (C2) against the H + /K + ATPase α - or catalytic subunit (HKα1) 53 , was used to identify the onset of HKα1 production during S .…”
Section: Methodsmentioning
confidence: 99%
“…Histological sections from the tail of the pancreas from each experimental group were stained with hematoxylin and eosin (Sigma Aldrich) and periodic acid–Schiff (PAS) (Sigma Aldrich) staining without diastase digestion (Fig. 2) using standard protocols and then evaluated . Sections were examined under a digital inverted light microscope (EVOS TM xl core; Fisher Scientific, Waltham, MA, USA) to compare acinar size, structure, and morphology (Fig.…”
Section: Methodsmentioning
confidence: 99%